1992
DOI: 10.1093/ajcp/98.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Acute Megakaryoblastic Leukemia Simulating Carcinoma

Abstract: Acute megakaryoblastic leukemia has emerged as an important subset of early childhood leukemia. It often presents a diagnostic dilemma because of its many morphologic manifestations and propensity to mimic metastatic carcinoma. An abdominal mass was identified by sonographic and computed tomographic scans in a 10-month-old girl, who had anemia and thrombocytopenia. An open biopsy of the 3-cm, peripancreatic mass showed cohesive nests and sheets of tumor cells with focal spindling and desmoplasia. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Some rather unusual findings in this study were skeletal pains from multiple osteolytic lesions [22,33,55], the presence of soft-tissue tumor [56] as in other types of AML M2, M5 [57], and of cohesive scanty clusters of 7-10 primitive-looking blast cells in BM aspirates, that may mimic metastatic solid tumors in the BM [58,59]. The presence of PDGF, TGF ␤, and fibronectin in extramedullary tumors suggests that specific expression of growth factor proteins by the leukemic cells may also selectively regulate tumor formation [60,61]. One form of differentiating the clusters of primitive-looking blast cells from the syncytial arrangement of cells of metastatic solid tumors in this study, was the finding of pseudo-rosettes consisting of megakaryoblasts, where all cells contained scant or moderate blue-gray cytoplasm, some showing central or peripheral platelet shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Some rather unusual findings in this study were skeletal pains from multiple osteolytic lesions [22,33,55], the presence of soft-tissue tumor [56] as in other types of AML M2, M5 [57], and of cohesive scanty clusters of 7-10 primitive-looking blast cells in BM aspirates, that may mimic metastatic solid tumors in the BM [58,59]. The presence of PDGF, TGF ␤, and fibronectin in extramedullary tumors suggests that specific expression of growth factor proteins by the leukemic cells may also selectively regulate tumor formation [60,61]. One form of differentiating the clusters of primitive-looking blast cells from the syncytial arrangement of cells of metastatic solid tumors in this study, was the finding of pseudo-rosettes consisting of megakaryoblasts, where all cells contained scant or moderate blue-gray cytoplasm, some showing central or peripheral platelet shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Penchansky et al reported three cases of AMKL in children with cohesive clusters of blast cell infiltration in bone marrow biopsy simulating metastatic carcinoma (7). Ashfaq et al reported an additional case of AMKL in an infant with an abdominal mass resembling epithelial malignant neoplasm (5). The exact mechanism that causes clumping of blast cells and the appearance of metastatic tumor in bone marrow aspiration and biopsy is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies demonstrated that megakaryocytic leukemia revealed the tumor‐forming nature of blastic cells 14,15 . Some adhesion molecules could possibly be ascribed to the feature 10,16–17 . The nature of blastic cells to adhere to each other may prevent them from entering peripheral blood circulation, resulting in difficulty in clinical diagnosis of blastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Some adhesion molecules could possibly be ascribed to the feature. 10,[16][17] The nature of blastic cells to adhere to each other may prevent them from entering peripheral blood circulation, resulting in difficulty in clinical diagnosis of blastic transformation. Blastic transformation in our patient was not diagnosed while she was alive; however, biopsy of her bone marrow, magnetic resonance imaging (MRI) and Ga scintigram were not performed.…”
Section: Discussionmentioning
confidence: 99%